A cross-sectional analysis of long-term exposure to ambient air pollution and cognitive development in children aged 3–4 years living in 12 low- and middle-income countries. (1st February 2023) - Odo, Daniel B.; Yang, Ian A.; Dey, Sagnik; Hammer, Melanie S.; van Donkelaar, Aaron; Martin, Randall V.; Dong, Guang-Hui; Yang, Bo-Yi; Hystad, Perry; Knibbs, Luke D.
Abstract: Exposure to ambient air pollution may affect cognitive functioning and development in children. Unfortunately, there is little evidence available for low- and middle-income countries (LMICs), where air pollution levels are highest. We analysed the association between exposure to ambient fine particulate matter (≤2.5 μm [PM2.5 ]) and cognitive development indicators in a cross-sectional analysis of children (aged 3–4 years) in 12 LMICs. We linked Demographic and Health Survey data, conducted between 2011 and 2018, with global estimates of PM2.5 mass concentrations to examine annual average exposure to PM2.5 and cognitive development (literacy-numeracy and learning domains) in children. Cognitive development was assessed using the United Nations Children's Fund's early child development indicators administered to each child's mother. We used multivariable logistic regression models, adjusted for individual- and area-level covariates, and multi-pollutant models (including nitrogen dioxide and surface-level ozone). We assessed if sex and urban/rural status modified the association of PM2.5 with the outcome. We included 57, 647 children, of whom, 9613 (13.3%) had indicators of cognitive delay. In the adjusted model, a 5 μg/m 3 increase in annual all composition PM2.5 was associated with greater odds of cognitive delay (OR = 1.17; 95% CI: 1.13, 1.22). A 5 μg/m 3 increase in anthropogenic PM2.5 was also associated with greater odds of cognitive delay (OR = 1.05; 95% CI: 1.00, 1.10). These results were robust to several sensitivity analyses, including multi-pollutant models. Interaction terms showed that urban-dwelling children had greater odds of cognitive delay than rural-dwelling children, while there was no significant difference by sex. Our findings suggest that annual average exposure to PM2.5 in young children was associated with adverse effects on cognitive development, which may have long-term consequences for educational attainment and health. Graphical abstract: Image 1 Highlights: The effects of ambient PM2.5 on early cognitive development are scarcely studied. We examined the association of PM2.5 and cognitive delay in low-income countries. Ambient PM2.5 exposure is associated with significant cognitive delay in children. The odds of cognitive delay associated with PM2.5 was greater in urban children.